PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR PERUSAHAAN DAERAH - Mardiyah Mardiyah; Cut Meutia Mustika Suri; Wahyu Agus Setiawan Suzan; Ratni Ratni (Cross-border, 2018)
This study aims to determine the effect both jointly and partially between motivation on employee performance in the Regional Company Offices of Pasar Kota Medan. This research uses quantitative methods with explanatory research using primary data and secondary data. The population in this study were employees at the Regional Company Offices of Pasar Kota Medan and as many as 82 employees were used as research samples. The data analysis technique used is multiple and partial linear regression using SPSS 24.0. The results of the regression analysis show that the independent variables are included in the regression model. The motivation variable has a significant value at 0.013. So it can be concluded that motivation affects employee performance (hypothesis 2 is accepted). Based on the t test, the motivation variable has a p-value (in the Sig. Column) 0.013 <0.05, which means significant, while t count 2.537> from the t table 1.991 means significant. This means that motivation has an effect on employee performance.